Growth and Development of Small Business Through Microfinance Activities in Nepal - Dhakal, Chandra Prasad (Interdisciplinary Journal of Management and Social Sciences, 2020)
Small businesses play important role for economic development and stability. It develops access in financial services through enhancing economic activities. The study analyzes the growth and development of small businesses that enhance through the support of micro finance in Nepal. Descriptive and inferential were used to collected data and collected data were analyzed through using multiple linear regression analysis. Only 124 small business owners were selected for this study. The study helps to find out the growth of microfinance institutions (MFIs) and small businesses in emerging economy in Nepal. It also assists MFIs to assess the effectiveness of their services and help to efficient utilization of available resources in the economy of Nepal.